Hubungan antara Aktivitas Fisik dan Status Gizi dengan Kualitas Hidup Kesehatan Siswa SMP dan SMA di Kecamatan Melonguane, Kabupaten Kepulauan Talaud - Elista Noviyanti Verlin Tangkuman; Aaltje Ellen Manampiring; Greta Jane Pauline Wahongan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
One of the health problems in adolescents is the health-related quality of life. Health-related quality of life can be influenced by many factors such as physical activity and nutritional status. The aim of this study was to analyze the correlation between physical activity and nutritional status with the health-related quality of life of junior and senior high school students in Melonguane District, Talaud Island Regency. Method: This type of research is quantitative, using observational methods with a cross-sectional approach which was carried out in April 2025. The sampling technique used consecutive sampling with a total of 310 respondents. The instruments in this research are questionnaires. Results: Data were analyzed using the chi square test with the results of the physical activity variable having a p value > 0,05 in all domains, namely the physical health domain (p=0,340), the psychology domain (p=0,652), the social relations domain (p=0,551) and the environmental domain (p=0,842). The nutritional status variable has a p value < 0,05 in the physical health domain (p = 0,004), and the environmental domain (p = 0,000) while the p value is > 0,05 in the psychological domain (p = 0,052) and social relations domain (p = 0,264). Conclusion: There is no correlation between physical activity and health quality of life in junior high and high school students in Melonguane District, Talaud Islands Regency and there is a correlation between nutritional status and health quality of life in junior high and high school students in Melonguane District, Talaud Islands Regency.